Dynamic Surface Reconstruction of Amphoteric Metal (Zn, Al) Doped Cu2O for Efficient Electrochemical CO2 Reduction to C2+ Products - Yufei Jia; Yunxuan Ding; Tao Song; Yunlong Xu; Yaqing Li; Lele Duan; Fei Li; Licheng Sun; Ke Fan (Advanced Science, 2023)
Abstract The recognition of the surface reconstruction of the catalysts during electrochemical CO2 reduction (CO2RR) is essential for exploring and comprehending active sites. Although the superior performance of Cu–Zn bimetallic sites toward multicarbon C2+ products has been established, the dynamic surface reconstruction has not been fully understood. Herein, Zn‐doped Cu2O nano‐octahedrons are used to investigate the effect of the dynamic stability by the leaching and redeposition on CO2RR. Correlative characterizations confirm the Zn leaching from Zn‐doped Cu2O, which is redeposited at the surface of the catalysts, leading to dynamic stability and abundant Cu–Zn bimetallic sites at the surface. The reconstructed Zn‐doped Cu2O catalysts achieve a high Faradaic efficiency (FE) of C2+ products (77% at –1.1 V versus reversible hydrogen electrode (RHE)). Additionally, similar dynamic stability is also discovered in Al‐doped Cu2O for CO2RR, proving its universality in amphoteric metal‐doped catalysts. Mechanism analyses reveal that the OHC–CHO pathway can be the C–C coupling processes on bare Cu2O and Zn‐doped Cu2O, and the introduction of Zn to Cu can efficiently lower the energy barrier for CO2RR to C2H4. This research provides profound insight into unraveling surface dynamic reconstruction of amphoteric metal‐containing electrocatalysts and can guide rational design of the high‐performance electrocatalysts for CO2RR.